Pisco and Toponimy: Impact of Brandy Routes in Development of Geographical Names and Places in Chile, Peru and Argentina [Pisco y Toponimia: Impacto de Las Rutas del Aguardiente en el Desarrollo de Nombres y Lugares Geográficos en Chile, Perú y Argentina] - Lacoste, P (Universidad de Tarapaca, 2014)
The Appellation of Origin (AO) Pisco (Chilean and Peruvian Brandy) is one of the oldest AO all over the world. Shaped by profound cultural, social, economic and political processes, this AO is a clear proof of the link of Chilean and Peruvian nations. The study subject of this paper lies on set of place names from the cities that compound the Brandy Road, which bound Argentina, Chile and Peru for more than 300 years. The thesis that we propose is that place names from the aforementioned cities reflect an important part of changes that shaped the cultural matrix of those three countries since Colonial Period until today. © 2014, Universidad de Tarapaca. All rights reserved.